Risk Exposures and Financial Spillovers in Tranquil and Crisis Times : Bank-Level Evidence - Poirson, Helene (IMF Working Papers; Working Paper ;, 2013)
For a sample of 83 financial institutions during 2003-2011, this paper attempts to answer three questions: first, what is the evolution of banks' stock price exposure to country-level and global risk factors as approximated by equity indices; second, which bank-specific characteristics explain these risk exposures; third, are there clusters of banks with equity price linkages beyond market risk factors. The paper finds a rise in sensitivities to both country and global risk factors in 2011, although on average to levels still below those of the subprime crisis. The average sensitivity to European risk, specifically, has been steadily rising since 2008. Banks that are reliant on wholesale funding, have weaker capital levels and low valuations, and higher exposures to crisis countries are found to be the most vulnerable to shocks. The analysis of bank-to-bank linkages suggests that any 'globalization' of the euro area crisis is likely to be channelled through U.K. and U.S. banks, with little evidence of direct spillover effects to other regions.